On the Optimality of Central Places - Quinzii, Martine; Thisse, Jacques-Francois (Econometrica, 1990)
Using the Eaton and Lipsey mode, one shows that a hierarchical system of central places is socially optimal: firms having less frequent purchases are clustered with firms having more frequent purchases in any configuration minimizing total transport and production costs